Photography off the scale technologies and theories of the mass image - Dvořák, Tomáš; Parikka, Jussi (Technicities : TECH, 2022)
Offers a new interdisciplinary perspective on the scale and quantity of images in contemporary visual cultureUnpacks the notion of the mass image through the lens of affective, representational, political, logistical and material economiesContains chapters by internationally renowned scholars as well as emerging researchers from the Czech Republic, UK and GermanyContributors include many of the key names who have been at the forefront of discussions about scale, digital visual culture, and photography and scale including Michelle Henning, Joanna Zylinska, Sean Cubitt, Joan Fontcuberta and Geoffrey BatchenFor people working in, researching or studying photography, media studies, digital culture and digital visual artsThese essays address the epistemological, aesthetic and political implications of various forms of scaling in both scholarly and artistic work. From the mass image in vernacular culture to transformations of photography in contexts of big data and artificial intelligence, they explore the massification of photography. They propose a shift into a fundamental re-evaluation of our theoretical coordinates so as to understand the underpinning media and culture of this change. Taken together, Photography Off the Scale calls for a reconsideration of both scholarly and artistic approaches and concepts in the face of our contemporary image excess